Upaya Pencegahan Penyakit Jantung Koroner Melalui Kegiatan Deteksi Dini Dislipidemia Pada Siswa Kelas XII SMA Negeri 1 Soropia - Usman, Julianti Isma Sari; Hasan, Fonnie Esther; Fauzi, Ahmad Zil; Hasan, Aswiro (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Dyslipidemia is a condition where the level of fat in the blood exceeds the normal level allowed in the body, therefore routine screening is important for early detection and can prevent or delay death. Screening for lipid disorders in young adults may indicate risk for future cardiovascular events. For screening dyslipidemia in high school adolescents. Implementation of community service is carried out by conducting assessments and permits for carrying out activities at SMA Negeri 1 Soropia, providing education about dyslipidemia and carrying out lipid profile checks and measuring blood pressure in class XII students of SMA Negeri 1 Soropia. Class XII students consisted of 24 boys (56%) and 19 girls (44%). From the results of early detection of dyslipidemia, it was found that 2 teenagers (5%) had symptoms of dyslipidemia and 41 people (95%) were normal and the results of blood pressure measurements were 21 people (48%) had normal blood pressure, 11 people (26%) had hypertension and 11 hypotensive people (26%). Early detection of dyslipidemia in class XII students provides an initial understanding of their health condition and encourages healthy lifestyle changes.ABSTRAKDislipidemia ialah kondisi dimana kadar lemak dalam darah melebihi kadar normal yang diperbolehkan di dalam tubuh, untuk itu skrining rutin penting untuk deteksi dini dan dapat mencegah atau menunda kematian. Skrining gangguan lipid pada dewasa muda dapat mengindikasikan risiko kejadian kardiovaskular di masa depan. Sebagai skrining dislipidemia pada remaja SMA. Pelaksanaan pengabdian kepada masyarakat dilakukan dengan penjajakan dan perizinan untuk pelaksanaan kegiatan di SMA Negeri 1 Soropia, memberikan edukasi mengenai dislipidemia serta melakukan pemeriksaan profil lipid dan pengukuran tekanan darah pada Siswa kelas XII SMA Negeri 1 Soropia. Siswa kelas XII yang terdiri dari 24 orang laki-laki (56%) dan 19 orang perempuan (44%). Dari hasil deteksi dini dislipidemia ditemukan 2 orang remaja (5%) dengan gejala dislipidemia dan 41 orang (95%) normal dan hasil pengukuran tekanan darah sebanyak 21 orang (48%) memiliki tekanan darah normal, hipertensi 11 orang (26%) dan 11 orang hipotensi (26%). Deteksi dini dislipidemia pada siswa kelas XII memberikan pemahaman awal mengenai kondisi kesehatan mereka dan mendorong perubahan gaya hidup sehat.